3-D wavelet coding of video with arbitrary regions of support - Minami, Gavin; Xiong, Zixiang; Wang, Albert; Mehrotra, Sanjeev (IEEE Transactions on Circuits and Systems for Video Technology, 2001)
We examine three-dimensional (3-D) wavelet coding of video with arbitrary regions of support (AROS). A critically sampled wavelet transform is applied to the AROS and a modiﬁed 3-D set partitioning in hierarchical trees (SPIHT) algorithm is used to quantize and code the wavelet coefﬁcients in the AROS only. Experiments show that, for typical MPEG-4 pre-segmented sequences, our proposed method can achieve a gain of up to 5.6 dB in average PSNR at the same rate over 3-D SPIHT coding of regular volumes that embed the AROS of the given video sequences.